Glyphosate residues in soil alter herbivore‐induced plant volatiles and affect predatory insect behaviour - Fuchs, Benjamin; Blande, James; Weijola, Valter (Wiley, 2026)
Plants under herbivore attack emit distinct blends of herbivore-induced plant volatiles (HIPVs) which serve as signalling cues for predatory insects. This concept of indirect plant defence has tremendous potential in sustainable insect pest control. It represents a cornerstone of alternatives to synthetic pesticides in integrated pest management (IPM) strategies. The composition of HIPVs determines the effectiveness of predatory insect attraction and is vulnerable to disturbance by multiple biotic and abiotic factors above- and belowground. Residues of the most widely used herbicide (glyphosate) are persistent pollutants in agricultural soils, where they increasingly affect plant physiology, with cascading effects on species interactions.
Here, we tested whether herbicide legacy in soil affects plant performance, aphid herbivory, and aphid-induced volatile organic compound (VOC) emissions in oat plants, and tested whether the preference of predatory ladybirds towards aphid-infested plants is affected by herbicide legacy in the soil.
Soil herbicide legacy reduced chlorophyll activity and plant height, but did not affect plant biomass nor aphid populations. Five compounds in the emitted VOC profile were significantly affected by soil history of herbicide use, which, in turn, affected ladybird orientation behaviour. In a choice assay, ladybirds preferred the odour of plants growing in herbicide-free soil.
These results reveal a subtle layer of effects of herbicide legacy in soil on emission of HIPVs, with cascading effects on predatory insect behaviour. Our results demonstrate that essential ecosystem services in the aboveground plant space, such as natural pest control, may be reduced by soil pollution with anthropogenic pesticides such as glyphosate, causing mismatches in plant-insect communication.